The terrible other: Wisdom from Mother Maria of Paris for contemporary missional engagement across boundaries - Rooms, Nigel (2025)
This article takes up a discussion which began in the journal Missiology around the employment of the concept of the ‘person of peace,’ taken from Luke 10: 6, in contemporary mission. It recognises the difficulties and pitfalls of encountering and engaging others, as neighbours across the boundary of the local church and rehearses some of the extant literature in the field. To develop the discussion the essay engages the writings of Mother Maria Skobtsova or Mother Maria of Paris (1891-1945), a 20th-century Orthodox saint and martyr, via some additional reflection of Rowan Williams upon her work. Several original ideas emerge from Mother Maria’s theology, not least, our solidarity as Christians with both Christ and his mother Mary. Such solidarity transfigures our possible relations with the neighbour as an icon of God, a ‘terrible’ (i.e. awesome) irreducible other. Encountering the neighbor is then an ascetic task which requires de-centering of the self/ego in order that the relationship may be entered into ‘free of mercenary desire’ and open up the life of Christ for all participants. Such a theology creates a fresh space for conviviality, in Ivan Illich’s terms across the boundary of the church.
Keywords: ascetic; Solidarity; Mother Maria Skobtsova; Neighbour; Person of peace